IDIOSTYLE PECULIARITIES IN TUNA KIREMITÇI`S “PRAYERS STAY THE SAME” - Zoia M. Kornieva; Iryna M. Borbenchuk (Alfred Nobel University Journal of Philology, 2022)
Present-day philological studies take into account ideological, aesthetic-philosophical and cultural factors that influence the work creation and the formation of the artist’s idiostyle. Prospects in the discovery and study of modern writers drew our attention to the figure of the Turkish novelist Tuna Kiremitçi. His novel “Prayers Stay the Same” (2007) is characterized by the coexistence of worldviews of the West and the East, determining the specificity of the choice of expressive linguistic means that serve for the embodiment of the ideas. The aim of the given article consists in identifying the peculiarities of the author’s style through complex analysis of the novel “Prayers Stay the Same” and singling out corresponding linguistic means. Kiremitçi’s idiostyle is characterized by the creation of a figurative system due to the author’s philosophical and religious views and genre-compositional features of the novel. Individualization of the style is facilitated by linguistic and stylistic means, among which the authors singled out toponyms, anthroponyms, foreign vocabulary, and youth slang as the most frequent ones. Linguopoetic features are marked by the use of anguage tools that have an aesthetic impact on the reader. The image of Istanbul reflects a set of cultural and personal traits, reveals historical events, promotes the formation of the heroines’ characters as well as conveys their spiritual secrets. The color of Oriental life is manifested in dialogues about the Turkish language and traditions, in quoting famous Turkish artists. Phraseologisms convey cultural and aesthetic values, outline the observations and worldview of both the Turkish people and the author himself. Spiritual ideals and guidelines are broadly represented in the novel in the texts of prayers, which are the author’s beliefs and searches for the answers for eternal questions, namely the essence of the prayer, faith, and the Almighty for an individual.